Comparative Study of IPTV & OTT Video From Technical and Business Aspects - Amali, Rully Burhan; Alamsyah, Ahmad Tossin; Sutiyo, Sutiyo (Syntax Literate, 2025)
The purpose of this research is to investigate the technical and business elements of IPTV and OTT Video, compare their advantages and disadvantages, and estimate their future growth potential. The research methods used are a literature review to collect relevant data and information and a SWOT analysis to evaluate strengths, weaknesses, opportunities, and threats. The results of the SWOT analysis show that IPTV has strengths in service quality, wide adoption in developed countries, and strong market growth in North America. However, there are weaknesses related to dependence on stable network infrastructure and geographical limitations. On the other hand, OTT video services offer high flexibility and accessibility, as well as a wide variety of content. However, they are also dependent on a stable internet connection and subscription fees may increase. In terms of opportunities, both services can capitalize on the growing demand for video content and technological advancements such as 5G networks. However, threats come in the form of intense competition between OTT service providers and strict regulations regarding copyright and privacy.